First Reported Case of Bacterial Endocarditis Attributable to Actinomyces meyeri - Susan Moffatt; A Raza Ahmen; Kevin Forward (Canadian Journal of Infectious Diseases)
A 48-year-old man presented to the Victoria General Hospital, Halifax, Nova Scotia in severe congestive heart failure. Echocardiographic studies revealed significant aortic valve insufficiency. Two anaerobic blood cultures performed two weeks apart were both positive for Actinomyces meyeri. The patient was treated with high dose intravenous penicillin. Three weeks after antibiotics were begun, he underwent aortic valve replacement. Intraoperative cultures were negative. Histopathological examination revealed findings in keeping with subacute bacterial endocarditis. The patient completed a six-week course of penicillin and was doing well three months after surgery. This is the first case of endocarditis attributable to A meyeri reported in the literature.